Business model you : a one-page method for reinventing your career - Clark, Tim, 1956-; Osterwalder, Alexander; Pigneur, Yves. (Hoboken, N.J. : Wiley, 2012)
Offers advice and inspiration for readers interested in changing their career or life paths, presenting techniques for designing and implementing a business model for an individual personal life.
Keywords: Career development; Success in business